Lowering Anxiety of Students Towards Science Using a Culturally Responsive Pedagogy: A Test of the Efficacy of Culturo-Techno-Contextual Approach - Adam, Umar; Akintoye, Hakeem; Oludipe, Olajumoke S.; Lameed, Soladoye; Bankole, Isaac; Abdulkareem, Kaothar; Assaf, Mohammed (Global READ Center, 2024)
Culturo-Techno-Contextual Approach (CTCA) is a culturally responsive teaching strategy that empowers African students to learn science meaningfully in the digital age. CTCA integrates culture, technology, and locational context to enhance students' comprehension of scientific concepts. This study examined the effectiveness of CTCA in reducing students learning anxiety towards science concept. A pretest-posttest, non-equivalent group design was adopted. The sample comprised 121 senior secondary II students (equivalent to grade 11) from two purposively selected schools in Lagos State. The Nutrition Anxiety Scale, which had a reliability coefficient of 0.70, was used data collection. The treatment period lasted four weeks following the pretest. The experimental group was taught using the CTCA, while the control group received conventional lecture-based instruction. The results revealed that those students who were taught using the culturo-techno-contextual approach had a significantly lower level of anxiety than the comparison group [F (1, 198) = 16.54; p < 0.05]. A statistically significant difference was not found based on gender [F(1,49)=.49; P >0.05]. Therefore, within the limitations of this study, it was concluded that CTCA is an effective teaching approach for lowering anxiety towards science. It is recommended that CTCA be adopted in teaching scientific concepts.